A Comparative Study of Intellectual Property Law: Uzbekistan, Europe, and the US - Jumakulov Muzaffar Javlonovich (Periodica Journal, 2025)
This article provides a comparative analysis of intellectual property (IP) law across Uzbekistan, Europe, and the United States, highlighting key similarities and differences in their legal frameworks. It examines the historical development, underlying principles, and practical applications of IP law within these regions. The study explores critical areas such as copyright, patents, and trademarks, alongside enforcement mechanisms and adherence to international agreements like the TRIPS Agreement and the Berne Convention. Particular emphasis is placed on how each jurisdiction addresses contemporary challenges, such as digital copyright, artificial intelligence-generated works, and cross-border IP disputes. By shedding light on the strengths and limitations of each system, the article aims to foster dialogue on potential legal reforms and encourage greater global harmonization in the protection of intellectual property rights
Keywords: Intellectual Property Law; Comparative Analysis; Uzbekistan Intellectual Property